2001
DOI: 10.1046/j.1365-2249.2001.01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant bacille Calmette–Guérin (BCG) expressing human interferon-alpha 2B demonstrates enhanced immunogenicity

Abstract: SUMMARYTo increase its immunostimulatory properties, BCG was genetically engineered to secrete recombinant human interferon-alpha 2B (rhIFN-a ) under control of the mycobacterial heat shock protein (hsp)60 promoter and the a antigen signal sequence. Expression of rhIFN-a was readily detectable by ELISA and on Western blotting. When compared with control BCG, rhIFN-a BCG was substantially more active in inducing the production of IFN-g and IFN-inducible protein 10 (IP-10) from human peripheral blood mononuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 30 publications
0
43
0
3
Order By: Relevance
“…In addition, IFN-α therapy has several drawbacks, such as high cost and repeated administration. A standard intravesical IFN-α instillation (combined with BCG) is carried out with 50-100 x 10 6 IU of IFN-α [23], although such a high dosage appears to be in excess of the actual amount needed for an effective antitumour immunity. Moreover, even a high dose of IFN-α may not be sufficient to induce optimal immunity because of its short retention time inside the bladder [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IFN-α therapy has several drawbacks, such as high cost and repeated administration. A standard intravesical IFN-α instillation (combined with BCG) is carried out with 50-100 x 10 6 IU of IFN-α [23], although such a high dosage appears to be in excess of the actual amount needed for an effective antitumour immunity. Moreover, even a high dose of IFN-α may not be sufficient to induce optimal immunity because of its short retention time inside the bladder [23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that IFN-g, TNF-a, and IL-12 are antiproliferative to cancer cells, as well as induce apoptosis (Thanhäuser et al, 1995;Brandau et al, 2000a). In addition, Luo et al (2001) showed that the restructuring of hIFNa-2b-rBCG effectively induced generation of hIFN-g, hTNF-a, and hIL-12, which was clearly higher than that in wild-type BCG and wild-type BCG plus IFN.…”
Section: Discussionmentioning
confidence: 90%
“…Immunotherapy with intravesical administration of Bacillus Calmette-Guérin (BCG) is an effective alternative approach to chemotherapy for managing superficial transitional cell carcinoma of the bladder (Alexandroff et al, 1999;Luo et al, 2001). In 1976, Morales et al first reported the intravesical use of BCG for treating superficial carcinoma of the bladder.…”
Section: Introductionmentioning
confidence: 99%
“…During its attachment to the bladder wall, rBCG-IFNα-2b continues to express IFNα-2b to a level high enough to induce immune responses to BCG. Although this IFNα-2b level is lower than the high dosage of exogenous IFNα-2b, a continuous low level of IFNα-2b is expected to suffice to function as a tumor suppressor (Luo et al, 2001). It has been reported that an IFNα-2b level as low as 100 U/ml is adequate for stimulating PBMC proliferation and the antitumor effects (Luo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs were prepared by glucan-diatrizoate meglumin density gradient centrifugation as described by Luo et al (2001) and cultured in RPMI-1640 (10% FBS) at a density of 10 6 cells/ml. A total of 100 μl of cells were added in triplicates into a 96-well plate.…”
Section: Measurement Of the Effects Of Rbcg-ifnα-2b On Proliferation mentioning
confidence: 99%